Challenges Faced by EFL Novice Teachers in Teaching English for Young Learners at Informal English Courses - Munawaroh, Kholilatul; Farihah, Safira Naila (English Language in Focus (ELIF), 2024)
This research is conducted to investigate the challenges experienced by EFL novice teachers in teaching English for Young Learners at informal English courses. This research was a qualitative study. The participants were selected because they had been teaching English to Young Learners in informal English course for more than six months. This research used qualitative research with semi-structured interview to collect the data. After gathering the data, the researcher analyzed all of the data by using the formula proposed by Renz (2018). The result of this research revealed that the participants faced difficulties in teaching English to Young Learners at English courses in four aspects include classroom language, classroom management, class activity and techniques of teaching.